ChemInform Abstract: Synthesis and Characterization of the Quaternary Scandium Uranium Selenide CsScUSe3(Se2). Issue 27 (18th June 2015) - Ward, Matthew D.; Lee, Minseong; Choi, Eun Sang; Ibers, James A.
Abstract The title compound is prepared by solid state reaction of a 1:1:3:4.7 molar mixture of U, Sc, Se, and CsCl, the latter acting as reactive flux (evacuated silica tubes, 1173 K, 6 h).